Digital workplace technologies and tacit knowledge sharing on employees’ digital competency: A systematic review - ABDULLAHI, Abdulazeez Kolapo; MAPHALA, Betty Portia (Edelweiss Applied Science and Technology, 2026)
This systematic review explores digital workplace technologies (DWT) and tacit knowledge sharing (TKS) on employees’ digital competency (EDC). The review aims to synthesize empirical evidence on how DWT and TKS influence EDC. We draw on Van Laar et al. [1]’s theoretical model of six domains of digital workplace transformation was adopted. The review adopted PRISMA guidelines to compile and analysed peer-reviewed articles published between 2022 and 2025, retrieved from Scopus, Web of Science, PsycINFO, and EBSCOhost databases. Out of 847 records identified, 31 studies met the inclusion criteria and were subjected to narrative synthesis. Findings revealed that DWT significantly supports digital competency by enabling continuous informal learning, collaborative digital routines, and ICT-mediated task execution. TKS positively reinforces digital self-efficacy, autonomy, and contextual tool proficiency through trust-driven peer exchange, and organizational knowledge enablers. The review was limited to English-language peer-reviewed articles and the dominance of cross-sectional survey designs, constituting 87.1% of the articles reviewed. This review advances knowledge by integrating a unified competency lens that explains digital competency as both a socio-technical and socially constructed outcome of DWT and TKS. It advances the Van Laar framework by integrating TKS as a digital-learning mechanism and provides multi-regional insights for future global research.